2008
DOI: 10.1109/tcbb.2007.1054
|View full text |Cite
|
Sign up to set email alerts
|

RnaPredict—An Evolutionary Algorithm for RNA Secondary Structure Prediction

Abstract: This paper presents two in-depth studies on RnaPredict, an evolutionary algorithm for RNA secondary structure prediction. The first study is an analysis of the performance of two thermodynamic models, Individual Nearest Neighbor (INN) and Individual Nearest Neighbor Hydrogen Bond (INN-HB). The correlation between the free energy of predicted structures and the sensitivity is analyzed for 19 RNA sequences. Although some variance is shown, there is a clear trend between a lower free energy and an increase in tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 47 publications
0
29
0
3
Order By: Relevance
“…We compare our results to those of RnaPredict in [42], where the best values obtained for 30 random seeds and 12 operator combinations are listed. Results for SARNA-Predict are taken from [35,36], where 100 runs were executed for various parameter combinations on each test sequence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compare our results to those of RnaPredict in [42], where the best values obtained for 30 random seeds and 12 operator combinations are listed. Results for SARNA-Predict are taken from [35,36], where 100 runs were executed for various parameter combinations on each test sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Massively parallel implementations [31] as well as efficient algorithms for small architectures exist [34]. RnaPredict and its parallelized version P-RnaPredict are GAs for predicting RNA secondary structure that have evolved to levels of prediction quality comparable to mfold ( [44,42]). Recently, the Simulated Annealing algorithm SARNA-Predict has been introduced ( [35,36]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike classical GA based methods, permutation based GAs seek to represent individuals as an ordered set of elements relating to the problem [17,16,19,13,18]. The classical representation of SAT individuals, as mentioned in Section 1.3, is a string of length n of 0s and 1s that corresponds to an assignment of the n variables.…”
Section: Representation Of the Problemmentioning
confidence: 99%
“…The more recent GAs works in this area are RnaPredict and its parallelized version PRnaPredict which proposed by Wiese and his students. They showed that the quality of their algorithm is comparable to Mfold [12,13]. SARNA-Predict is a SA algorithm has been introduced in [3,14] which has used to predict RNA secondary structure that has a low free energy and a high number of correctly predicted base pairs when compared to the known native structures.…”
Section: Rna Secondary Structure Prediction Algorithmsmentioning
confidence: 99%